2011
DOI: 10.1371/journal.pone.0024375
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of NDRG1 Promotes Migration of Cancer Cells during Reoxygenation

Abstract: One characteristic of tumor microenvironment is oxygen fluctuation, which results from hyper-proliferation and abnormal metabolism of tumor cells as well as disorganized neo-vasculature. Reoxygenation of tumors can induce oxidative stress, which leads to DNA damage and genomic instability. Although the cellular responses to hypoxia are well known, little is known about the dynamic response upon reoxygenation. In order to investigate the transcriptional responses of tumor adaptation to reoxygenation, breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…In the present study, we showed that NDRG1 mRNA expression was downregulated upon re-oxygenation, which is in agreement with a previous study concerning decreased NDRG1 mRNA expression in the breast cancer cell line MCF-7 after re-oxygenation (51). Therefore, NDRG1 is considered to be an O 2 -responsive gene, linked to tumor adaptation towards re-oxygenation (51,52).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we showed that NDRG1 mRNA expression was downregulated upon re-oxygenation, which is in agreement with a previous study concerning decreased NDRG1 mRNA expression in the breast cancer cell line MCF-7 after re-oxygenation (51). Therefore, NDRG1 is considered to be an O 2 -responsive gene, linked to tumor adaptation towards re-oxygenation (51,52).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, NDRG1 is considered to be an O 2 -responsive gene, linked to tumor adaptation towards re-oxygenation (51,52). However, our western blot results did not support this notion, and suggest posttranscriptional regulation of NDRG1 expression.…”
Section: Discussioncontrasting
confidence: 68%
“…Previously, our studies indicated that NDRG1 plays a critical role in tumor adaptation to oxygen fluctuations 39 . Here we provided the first evidence that AHR mediates cobalt-mimetic hypoxia induction of NDRG1 through an AHR/ARNT binding site in the promoter using various promoter truncations or site-mutation constructs.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we used genome-wide expression microarrays to investigate the dynamics of gene profiling during reoxygenation in breast cancer MCF-7 cells, and demonstrated that N-myc downstream-regulated gene 1 ( NDRG1 ) was involved in tumor adaptation to reoxygenation7. NDRG1 is a 43-kD protein composed of 394 amino acids, and is highly conserved among multicellular organisms.…”
mentioning
confidence: 99%